Erythrocyte ion transport alterations in hypertriglyceridaemic rats - Kunes, J; Bin Talib, H K; Dobesová, Z; Vrána, A; Zicha, J (Clinical science (London, England, 1994)
1. Hypertension appears to be associated with both abnormalities in ion transport and disturbances in lipid metabolism. The aim of the present study was to search for alterations in erythrocyte ion transport in hereditary hypertriglyceridaemic rats. This strain is characterized by a pronounced elevation of blood pressure which correlates with the plasma triacylglycerol level. 2. Erythrocyte Na+ content was elevated in hypertriglyceridaemic rats due to an increased ouabain-resistant Na+ net uptake. This was caused not only by the acceleration of bumetanide-sensitive Na+ inward co-transport, but also by the augmentation of bumetanide-resistant Na+ inward leak. A moderate enhancement of bumetanide-sensitive Rb+ uptake was seen in hypertriglyceridaemic animals, but there were no changes in bumetanide-resistant Rb+ leak. 3. The plasma triacylglycerol level correlated positively not only with blood pressure (P < 0.001) but also with ouabain-resistant Na+ transport (P < 0.002), bumetanide-sensitive Na+ and K+ (Rb+) co-transport (P < 0.01 and P < 0.001, respectively), bumetanide-resistant Na+ leak (P < 0.02) and erythrocyte Na+ content (P < 0.05). 3. Thus the association of augmented ouabain-resistant Na+ transport with elevated blood pressure in this form of experimental hypertension might be mediated by genetic disorders of lipid metabolism.
Keywords: Potassium; Male; Rats, Wistar; draslík; ouabain; Rubidium; hypertriglyceridemie; Hypertriglyceridemia; rubidium; mužské pohlaví; sodík; Ouabain; potkani Wistar; iontový transport; krysa rodu Rattus; Sodium; Bumetanide; Animals; krevní tlak; Ion Transport; zvířata; Rats; Blood Pressure; erytrocyty; Erythrocytes; bumetanid